KELAYAKAN FINANSIAL PROSESSING KRIPIK KENTANG DARI ENAM BAHAN BAKU VARIETAS KENTANG YANG BERBEDA - Asma Sembiring (UIN Sunan Gunung Djati Bandung, 2023)
One kind of snack that Indonesian people often consume is potato chips. Mostly, potato chips processors use the vegetable potato 'Granola variety' as the raw material. Meanwhile, a kind of potato variety that fits the chips raw material is Atlantik. Nevertheless, the availability is limited. Indonesian Vegetables Research Insitute (IVegRI) has an effort to create potato varieties that are suitable as the food industrial raw material. The research objective was to identify the financial feasibility of potato chip processing from six different potato varieties' raw materials. The study was conducted in Lembang sub-district, West Java Province, from April to August 2020. Six potato varieties, namely AR 08, Sangkuriang, Medians, Papita, Spudy and Atlantik, were planted in IP2TP Margahayu, Lembang-West Java area, 100 m2 for each variety. After harvesting, the potatoes were processed as chips. The financial feasibility of potato chips processing was calculated using the cost and revenue of potato chips processing analysis and the Benefit-Cost Ratio. The finding showed that Medians generated the highest revenue of the six potato variety raw material. It was 1,113,250 IDR, with the profit being 193,554 IDR. In the meantime, based on B/C ratio analysis, five profitable potato varieties used as the chip's material were Medians, Papita, Spudy, Sangkuriang and Atlantik, with the B/C score > 1. The three highest B/C score were Spudy, Atlantik and Medians. The score was 1.41, 1.24 and 1.21, respectively.